Intravoxel incoherent motion MRI for the differentiation between mass forming chronic pancreatitis and pancreatic carcinoma - Klauß, Miriam; Lemke, Andreas; Grünberg, Katharina; Simon, Dirk; Re, Thomas J.; Wente, Moritz N.; Laun, Frederik B.; Kauczor, Hans-Ulrich; Delorme, Stefan; Grenacher, Lars; Stieltjes, Bram (Investigative radiology, 2011)
Purpose: To determine which of the quantitative parameters obtained from intravoxel incoherent motion diffusion weighted imaging (DWI) is the most significant for the differentiation between pancreatic carcinoma and mass-forming chronic pancreatitis. - Materials and Methods: Twenty-nine patients with pancreatic masses were included, 9 proved to have a mass-forming pancreatitis and 20 had a pancreatic carcinoma. The patients were studied using intravoxel incoherent motion DWI with 11 b-values and the apparent diffusion coefficient (ADC), the true diffusion constant (D) and the perfusion fraction (f) were calculated. The diagnostic strength of the parameters was evaluated using receiver operating characteristic analysis. - Results: The ADC in chronic pancreatitis was higher than in pancreatic carcinoma with significant differences at b = 50, 75, 100, 150, 200, 300 s/mm2 (ADC50 = 3.17 ± 0.67 vs. 2.55 ± 1.09, ADC75 = 2.46 ± 0.4 vs. 1.93 ± 0.52, ADC100 = 2.28 ± 0.48 vs. 1.73 ± 0.45, ADC150 = 1.97 ± 0.26 vs. 1.63 ± 0.40, ADC200 = 1.98 ± 0.24 vs. 1.53 ± 0.28, and ADC300 = 1.76 ± 0.19 vs. 1.46 ± 0.31 × 10−3 mm2/s). No significant differences were found at b = 25, 400, 600, and 800 s/mm2 (ADC25 = 4.69 ± 0.65 vs. 4.04 ± 1.35, ADC400 = 1.57 ± 0.21 vs. 1.37 ± 0.30, ADC600 = 1.38 ± 0.18 vs. 1.24 ± 0.25, and ADC800 = 1.27 ± 0.10 vs. 1.18 ± 0.19 × 10−3 mm2/s) nor using ADCtot (1.42 ± 0.23 vs. 1.28 ± 0.12 × 10−3 mm2/s). The perfusion fraction f was significantly higher in pancreatitis compared with pancreatic carcinoma (16.3% ± 5.30% vs. 8.2% ± 4.00%, P = 0.0001). There was no significant difference between groups for D (1.07 ± 0.224 × 10−3 mm2/s for chronic pancreatitis and 1.09 ± 0.3 × 10−3 mm2/s for pancreatic carcinoma, P = 0.66). For f, the highest area under the curve (0.894) and combined sensitivity (80%) and specificity (89.9%) were found. - Conclusions: There were significant differences in ADC50-300 between chronic pancreatitis and pancreatic carcinoma. Because D is not significantly different between groups, differences in ADC can be attributed mainly to differences in perfusion. The perfusion fraction f proved to be the superior DWI-derived parameter for differentiation of mass-forming pancreatitis and pancreatic carcinoma.
Gesehen am 08.08.2022